Conocimiento y práctica del uso de equipos de protección individual en marco del COVID-19, en enfermeros de la unidad de cuidados intensivos, Hospital Regional Loreto 2022 - Ushiñahua Pinedo, Jhomnie (2024)
The objective of the study was to determine the relationship between the knowledge and practice of the use of personal protective equipment framed in COVID-19, in the Intensive Care Unit at the Regional Hospital of Loreto 2022. The study had a quantitative approach, prospective, non-experimental design. of a correlational descriptive nature, the population and sample consisted of 30 nursing professionals. The results were: 70.0% of nurses had high knowledge about the use of personal protective equipment in the context of COVID-19, 20.0% had medium knowledge, and 10.0% had low knowledge; 60.0% carried out efficient practice of using personal protective equipment, 23.3% carried out it regularly, and 16.7% performed it poorly and when testing the hypothesis using Kendall's tau b statistical test, it was found positive significance was obtained between knowledge and use of personal protective equipment (t = 0.421; > 0.05). The study concludes that the high level of knowledge is significantly related to efficient practice in the use of personal protective equipment in the context of COVID-19 in nurses at the Loreto Regional Hospital 2022.